2006
DOI: 10.1152/jn.00050.2005
|View full text |Cite
|
Sign up to set email alerts
|

Activity of the Motor Cortex During Scratching

Abstract: . In awake cats sitting with the head restrained, scratching was evoked using stimulation of the ear. Cats scratched the shoulder area, consistently failing to reach the ear. Kinematics of the hind limb movements and the activity of ankle muscles, however, were similar to those reported earlier in unrestrained cats. The activity of single neurons in the hind limb representation of the motor cortex, including pyramidal tract neurons (PTNs), was examined. During the protraction stage of the scratch response, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 76 publications
0
2
0
Order By: Relevance
“…Importantly, the ACC receives robust projections from the thalamus (Lee et al 2007), forms multiple reciprocal connections with other cortical areas (Vogt 2005), including the motor cortex, Leknes et al 2007), and contributes to descending facilitation of spinal cord transmission (Calejesan et al 2000). Accordingly, we observed that scratching behavior corresponded to ACC activity, and scratching has been shown to correspond with motor cortex activity (Sirota et al 2006). Similarly, neuroimaging studies have observed co-activation of the ACC, supplementary, and pre-motor areas in correspondence with the urge to scratch in humans (Hsieh et al 1994;Leknes et al 2007).…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Importantly, the ACC receives robust projections from the thalamus (Lee et al 2007), forms multiple reciprocal connections with other cortical areas (Vogt 2005), including the motor cortex, Leknes et al 2007), and contributes to descending facilitation of spinal cord transmission (Calejesan et al 2000). Accordingly, we observed that scratching behavior corresponded to ACC activity, and scratching has been shown to correspond with motor cortex activity (Sirota et al 2006). Similarly, neuroimaging studies have observed co-activation of the ACC, supplementary, and pre-motor areas in correspondence with the urge to scratch in humans (Hsieh et al 1994;Leknes et al 2007).…”
Section: Discussionmentioning
confidence: 64%
“…Accordingly, we observed that scratching behavior corresponded to ACC activity, and scratching has been shown to correspond with motor cortex activity (Sirota et al . ). Similarly, neuroimaging studies have observed co‐activation of the ACC, supplementary, and pre‐motor areas in correspondence with the urge to scratch in humans (Hsieh et al .…”
Section: Discussionmentioning
confidence: 97%